Trends of smoking and alcohol consumption after acute myocardial infarction – a gerontological meta-analysis - György, Jóna (Magyar Gerontológia, 2023)
The core aim of this conference presentation is to demonstrate how health behaviors of elderly social groups could be shifted by perceived social support (PSS) after acute myocardial infarction (AMI). More precisely, this presentation focuses on examining how elderly people could quit smoke and accept moderate alcohol consumption by PSS to improve their complex health conditions.